2010
DOI: 10.3109/02841851.2010.518975
|View full text |Cite
|
Sign up to set email alerts
|

Is there a role for BLADE acquisition in T2-weighted breast MRI?

Abstract: the performance of BLADE is superior to routine T2W images in eliminating motion artifacts, provides better SNRs, shows detailed pectoral muscle contours, and may be the sequence of choice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…This concurs with the findings reported by Ozcam et al. ( 17 ) in their study on 44 breast exams. They observed that BLADE acquisition technique provides better pectoral muscle contour assessment and better SNRs, that are essential for a good evaluation of breast exams, in particular when implants are present.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…This concurs with the findings reported by Ozcam et al. ( 17 ) in their study on 44 breast exams. They observed that BLADE acquisition technique provides better pectoral muscle contour assessment and better SNRs, that are essential for a good evaluation of breast exams, in particular when implants are present.…”
Section: Discussionsupporting
confidence: 94%
“…Its use is spreading over the last years with new software developments as an alternative non-Cartesian k -space trajectory scheme in brain, cervical spine and head MRI studies ( 9 , 14 ) , and more recently in the abdomen ( 11 , 15 ) and female pelvis ( 16 ) exams. To our knowledge, there is only one study which reports on the application of BLADE in breast MRI ( 17 ) . Prior studies evaluating BLADE in non-breast applications have reported a reduction of motion artifacts and improvement in qualitative analysis of T2-weighted sequences ( 8 - 11 , 13 - 17 ) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, these sequences reduce the artifacts due to swallowing in cervical spine MRI [21]. According to Ozcan et al, the performance of BLADE is superior to routine T2-weighted images in eliminating motion artifacts, and it provides better signal-to-noise ratios (SNRs) [23].…”
Section: Introductionmentioning
confidence: 99%